2008
DOI: 10.1590/s0101-98802008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de mau prognóstico nas peças operatórias de pacientes submetidos ao tratamento cirúrgico do câncer colorretal

Abstract: Descritores: Câncer colorretal, prognóstico, linfonodos, estadiamento do câncer, histopatologia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
(96 reference statements)
2
9
0
Order By: Relevance
“…When the groups were stratified by age, we found that patients older than 50 years were significantly more affected by CRC (P = 0.0001), confirming that age is a risk factor for the development of CRC, as demonstrated in several previous studies (Farhoud et al, 2002;Volpato and Koch, 2008;Park et al, 2011).…”
Section: Clinical Featuressupporting
confidence: 85%
See 2 more Smart Citations
“…When the groups were stratified by age, we found that patients older than 50 years were significantly more affected by CRC (P = 0.0001), confirming that age is a risk factor for the development of CRC, as demonstrated in several previous studies (Farhoud et al, 2002;Volpato and Koch, 2008;Park et al, 2011).…”
Section: Clinical Featuressupporting
confidence: 85%
“…Mucinous tumors are defined by the presence of extracellular mucin at more than 50% of the tumor volume and account for approximately 8-20% of all CRCs (Volpato and Koch, 2008;Rocha et al, 2010). The presence of signet ring cells is a variant of mucinous tumors and is found in 0.1-2.4% of CRCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that an increase in the composition of the tumor stroma and a reduction in epithelial cellularity were significantly correlated with genetic signatures related to epithelial-mensenchymal transition (12). The depth of invasion through the intestinal wall and the presence of lymph node metastases, which are recognized as the most important independent prognostic factors in CRC, related to survival and risk of recurrence, in addition to indicating the therapeutic approach (22,43,44), were significantly related to the percentage of stroma. All pT1 patients were stroma-low, while 75.6% of the pT2 patients were stroma-low.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,14,15 The established prognostic factors include depth of tumor invasion of the intestinal wall and presence of nodal metastases (most relevant), presence of venous or lymphatic invasion, and the degree of tumor differentiation. [16][17][18] Anatomopathological staging of the surgical specimen represents the main tool to be used in isolation to infer the prognosis and survival of patients with CRC, representing the independent dominant variable that most affects survival. 18 It is also considered the most important prognostic factor, guiding the choice of the ideal cancer treatment.…”
Section: Introductionmentioning
confidence: 99%